PERAN PESANTREN DALAM PEMBENTUKAN KARAKTER SANTRI : TINJAUAN ASPEK PSIKOLOGIS - Fauzi, Ahmad; B. Safuri; Umi Kultsum (AL MURABBI, 2025)
Pesantren, as a traditional Islamic educational institution, plays a crucial role in shaping the character and mental well-being of santri (students). This study aims to explore how the pesantren environment contributes to the development of personality that is deeply rooted in psychological and spiritual values. Employing a qualitative approach through a case study model, data were gathered using in-depth interviews, participatory observation, and documentation within a selected pesantren setting. The findings reveal that pesantren shape the character of santri through various integrated mechanisms. These include the internalization of religious values, consistent implementation of discipline, and the habituation of positive behaviors such as honesty, responsibility, cooperation, and respect. In addition, the presence of exemplary role models—such as ustadz (religious teachers) and kyai (leaders)—fosters an environment of moral learning and emotional guidance. These figures provide daily examples of patience, integrity, and self-control, which become internalized by the santri through constant interaction and imitation. Moreover, the pesantren offers a spiritually conducive environment supported by structured routines in worship, communal living, and mutual support among peers. This unique ecosystem fosters not only religious knowledge but also strengthens mental resilience, self-confidence, emotional regulation, and social empathy among students. Santri learn to manage stress, overcome personal challenges, and develop a stable and integrated personality. Therefore, pesantren should not be viewed merely as centers for Islamic instruction, but also as holistic institutions for psychological growth, promoting comprehensive character formation, mental health awareness, and emotional maturity in a balanced and sustainable manner.